The Development Electronic Module of History using ADDIE Model - N Najuah; Ricu Sidiq; Pristi Suhendro Lukitoyo (International Journal of Educational Research & Social Sciences, 2021)
Students need learning aids that are by the development of communication technology during the corona disease pandemics. In history subjects, there are not many electronic modules developed for unit semester learning outcomes. This study aimed to develop an Electronic Module of History (EHM/MES) using The ADDIE model as a learning aid for high school students and to determine its feasibility and attractiveness. This study used to research and development method. The ADDIE development model includes 5 activity sequel steps. The steps must be carried out in order and cannot be randomized. We used interviews and questionnaires to collect data from education experts, Indonesian History teachers, and students. The results showed that the MES developed could be used by XI grade high school students in the Indonesian History subject for semester 1. The product packaged in 4 separate chapters according to the curriculum analysis. Based on the results of data analysis and discussion of the MES development process, can be explained that (1) expert testing on the validation results of material experts was a very great criterion, media experts and learning design experts werevery great criteria, (2) The level of attractiveness of the MES in individual trials of three Indonesian history subject educators gets an average result of with the category interesting, The small group trial from educators got results so attractive criteria, and the use of digital modules at the implementation stage, students had attractiveness test results highly attractive criteria. The limitation of this study is that the MES developed has not been tested for its effectiveness because of the difficulty in controlling the test activities due to the learning system policy during the current pandemic and the development process is still using unpaid applications. The novelty of value from this MES is that it can hyperlink and hypertext so that the display of the module becomes more attractive.